Overcoming immunoescape mechanisms of BCL1 leukemia and induction of CD8+ T-cell-mediated BCL1-specific resistance in mice cured by targeted polymer-bound doxorubicin - Kovář, Marek; Tomala, Jakub; Chmelová, Helena; Kovář, Lubomír; Mrkvan, Tomáš; Josková, Radka; Jirásková-Zákostelská, Zuzana; Etrych, Tomáš; Strohalm, Jiří; Ulbrich, Karel; Šírová, Milada; Říhová, Blanka (Cancer research, 2008)
BALB/c mice bearing syngeneic BCL1 leukemia, a mouse model of human chronic lymphocytic leukemia, were treated with polymer-bound doxorubicin conjugate targeted with BCL1-specific monoclonal antibody. Such treatment can cure up to 100% of mice and the cured mice show long-lasting resistance to BCL1 leukemia. We show that both CD4+ and CD8+ T cells are required for establishment of the resistance, but only CD8+ T cells are necessary for its maintenance. BCL1 cells express MHC class I and II and also costimulatory molecules CD80 and CD86, which can aid eliciting of antitumor response. On the other hand, BCL1 cells also use several immunoescape mechanisms, such as expression of PD-L1, PD-L2, and interleukin-10. BCL1 cells thus can be recognized by BCL1-specific T cells, but instead of effective priming, such T cells are anergized or deleted by apoptosis. Moreover, BCL1 leukemia progression is accompanied by robust expansion of CD4+CD25+Foxp3+ regulatory T (Treg) cells. Although it has been shown that depletion of Treg cells in tumor-bearing mice can retard tumor growth, direct evidence that expansion of Treg cells can promote tumor growth was lacking. In this study, we provide first direct evidence that expanded Treg cells can indeed promote tumor progression by using mice with selectively expanded Treg cells before inoculation of BCL1 leukemia. Finally, we have also shown that elimination of some immunoescape mechanism (e.g., deletion of Treg) can significantly improve the therapeutic outcome of chemotherapy.
Keywords: Polymethacrylic Acids; doxorubicin; monoklonální protilátky; imunokonjugáty; protinádorová antibiotika; regulační T-lymfocyty; Leukemia, B-Cell; myši inbrední BALB C; CD8-Positive T-Lymphocytes; Mice, Inbred BALB C; T-Lymphocytes, Regulatory; Animals; kyseliny polymethakrylové; CD8-pozitivní T-lymfocyty; ženské pohlaví; únik nádoru z imunitní kontroly; zvířata; Antibiotics, Antineoplastic; myši; Antibodies, Monoclonal; Mice; Female; Doxorubicin; Tumor Escape; leukemie B-buněčná; Immunoconjugates